Pregnancy and antibody-mediated CNS disorders: What do we know and what should we know? - Cortese, Rosa; Mariotto, Sara; Mancinelli, Chiara Rosa; Tortorella, Carla (Frontiers in neurology, 2022)
Antibody-mediated central nervous system (CNS) disorders including those associated with aquaporin-4 or myelin oligodendrocyte glycoprotein IgG and autoimmune encephalitis often affect women of childbearing age. Pathogenic antibodies of these diseases can potentially alter reproductive functions and influence fetal development. Hormonal changes occurring during pregnancy may modify the course of autoimmune diseases by influencing relapse risk, attack severity, and affect the delivery and postpartum period. Moreover, balancing treatment related safety issues with the risk of potentially disabling relapses during pregnancy and breastfeeding are major challenges. Intentional prenatal, gestational, and post-partum counseling is paramount to address these issues and mitigate these risks. Fortunately, new insights on risk factors for adverse pregnancy outcomes and possible preventive strategies are emerging. This review aims to summarize the interplay between antibody-mediated CNS disorders and pregnancy during the prenatal, gestational, and postpartum periods, highlight current treatment recommendations, and discuss future areas of research.